Diffuse Large B-Cell Lymphoma, Not Otherwise Specified (DLBCL NOS) Presenting as Multiple Subcutaneous Nodules: An Unusual Cutaneous Presentation of Systemic Disease - Tavberidze, Nika; Bennett, Daniel D.; Matson, Daniel R. (Case Reports in Pathology, 2023)
Diffuse large B-cell lymphoma, not otherwise specified (DLBCL NOS) is the most common lymphoid malignancy in the Western world and classically presents as a rapidly enlarging nodal or extranodal mass. Cutaneous involvement by systemic DLBCL NOS is an infrequent clinical presentation, encountered in only 1.5-3.5% of cases, while disseminated cutaneous disease with multiple subcutaneous nodules at the time of diagnosis is unusual and can present a diagnostic challenge. The differential diagnosis when encountering a high-grade B-cell malignancy at a cutaneous site is broad and includes primary cutaneous follicle center lymphoma (PCFCL), primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBCL-LT), high-grade B-cell lymphoma with MYC and BCL2 rearrangements (HGBCL-MYC/BCL2), and other potential entities which must all be carefully considered before rendering a final diagnosis. In this report, we describe the case of a 69-year-old man who was seen at our hospital due to generalized weakness and was found to have multiple subcutaneous nodules representing disseminated DLBCL NOS. The case was complicated by concurrent monoclonal B-cell lymphocytosis involving the bone marrow.